Efficacy of conventional and nano-formulated seed treatments for the control of Hessian fly (Mayetiola destructor) in wheat - Amego, Kokou Selom (My University, 2025)
The Hessian fly is one of the most destructive pests of wheat, causing significant yield losses worldwide. The most effective management methods include using resistant varieties and applying cultural practices. However, resistant varieties often produce lower yields than susceptible ones, and wheat resistance can be significantly affected by temperature. Therefore, seed treatments, especially neonicotinoids, may serve as an effective strategy against Hessian flies. Still, their efficacy is only observed up to four weeks after planting, and there has been no recent evaluation of their effectiveness. This study aims to reassess the current effectiveness of conventional neonicotinoid insecticides and to develop and test carbon nano-insecticides both in the laboratory and in the field. Initially, two conventional neonicotinoid-treated seeds at the label-recommended rate were evaluated: commercially treated thiamethoxam and laboratory-treated imidacloprid. Results showed that thiamethoxam-treated seeds were highly effective, maintaining infestation levels near zero for up to 30 days. Untreated seeds showed infestation levels over 90%. Imidacloprid-treated seeds were moderately effective, with infestation levels ranging from 30% to 60%. Additionally, carbon nano-imidacloprid was tested at both the commercially recommended rate and half that rate in the laboratory and the field. Results indicated that nano-imidacloprid at a high commercial rate was the most effective in controlling Hessian fly infestation in both settings. The nano-imidacloprid at half the rate showed somewhat lower control levels compared to the high rate but was similar to commercial imidacloprid seed treatment.
Keywords: Carbon nano-insecticide; Hessian fly; Neonicotinoid; Seed treatment; Wheat